2020
DOI: 10.1177/0267659120907746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for adverse outcome in extracorporeal membrane oxygenation–supported elderly postcardiotomy patients

Abstract: Background: Recently extracorporeal membrane oxygenation is becoming the commonly used mechanical assist device for the treatment of severe cardiogenic shock in postcardiotomy patients. Evaluation of risk factors of negative outcome would be beneficial in decision-making in the elderly patient population. Methods: This was a retrospective single-centre analysis of elderly patients who underwent extracorporeal membrane oxygenation treatment for refractory cardiogenic shock in a tertiary care centre. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…A total of 273 articles were yielded from a systematic review of the literature and 31 studies were considered suitable for the present analysis. The investigators of 10 studies 2,[8][9][10][11][12][13][14][15][16] provided data for the present analysis. The types and quality of the included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 273 articles were yielded from a systematic review of the literature and 31 studies were considered suitable for the present analysis. The investigators of 10 studies 2,[8][9][10][11][12][13][14][15][16] provided data for the present analysis. The types and quality of the included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 patients (80.0%) who underwent reoperation survived to discharge. Patients undergoing elective surgery had a significantly shorter duration of postoperative mechanical ventilation (PMV) (14 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] vs. 24 hours, p < 0.001) and length of intensive care unit stay (3 [2-6] vs. 5 [3][4][5][6][7][8] days, p ¼ 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…16 Although current literature suggests that the age itself does not affect the outcomes of extracorporeal life support (ECLS) in the older patients, the baseline condition is what influences the survival after ECLS therapy in older patients. 17,18 In the unmatched cohort, a total of 12 patients (1.7%) required ECLS postoperatively. Among these patients, only one patient survived to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant higher lactate level before ECMO initiation was found in the septuagenarian patient group. High lactate level before the initiation of ECMO support was shown to be an important prognostic factor of unfavorable outcomes in the elderly population [ 17 , 18 ]. Multivariate analysis revealed that intubation time before ECMO initiation was a significant predictor of hospital survival.…”
Section: Discussionmentioning
confidence: 99%